Oportunidades y dificultades del nearshoring en México - Gereffi, Gary (El Colegio de México A.C., 2025)
Mexico has had an exceptionally close relationship with the United States (US) for many decades. Recent calls in the US for a new wave of “nearshoring” to help the American economy rebuild its fragmented and vulnerable supply chains following a series of disruptions and geopolitical shifts linked to the COVID-19 global pandemic, the rise of economic nationalism, China’s emergence as a global technological superpower, and growing regional conflicts raise both opportunities and challenges for Mexico. This article reviews Mexico’s bilateral economic ties with the US economy in the postwar period to highlight patterns and lessons that can be learned to deal with the current conjuncture. The global value chains (GVC) approach is utilized to show how recent US industrial and trade policies focus on a series of strategic industries such as semiconductors, automobiles, pharmaceuticals, and critical minerals in which Mexico has much to offer. However, international competition and US political dynamics require a more active and comprehensive development strategy in Mexico to achieve both development and innovation benefits.